1996
DOI: 10.1021/la9515682
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of the L Phase and the Hexagonal, Lamellar, and Cubic Liquid Crystals of the CTAB/Benzyl Alcohol/Water System

Abstract: The rheological properties of different phases of the CTAB/benzyl alcohol/water system have been studied. The L phase, except the samples close to the hexagonal liquid crystal, is a viscous fluid with a characteristic Newtonian behavior. On the contrary, the L phase samples close to the hexagonal phase are pseudoplastic fluids built up of cylindrical micelles with elastic properties. The hexagonal liquid crystal behaves as a shear thinning fluid with a well-defined zero-shear-rate viscosity, while the lamellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
88
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 26 publications
20
88
0
1
Order By: Relevance
“…Bicontinuous cubic liquid crystals have been reported to exhibit a viscoelastic spectrum similar to that described above for the I 1 ' mesophase (Radiman et al, 1994), (Montalvo et al, 1996). Their viscoelastic spectrum fit the Maxwell model, with a single relaxation time, or the Generalized Maxwell model with only two relaxation times.…”
Section: Hexagonal Liquid Crystals (H 1 ) (H 2 )mentioning
confidence: 56%
See 1 more Smart Citation
“…Bicontinuous cubic liquid crystals have been reported to exhibit a viscoelastic spectrum similar to that described above for the I 1 ' mesophase (Radiman et al, 1994), (Montalvo et al, 1996). Their viscoelastic spectrum fit the Maxwell model, with a single relaxation time, or the Generalized Maxwell model with only two relaxation times.…”
Section: Hexagonal Liquid Crystals (H 1 ) (H 2 )mentioning
confidence: 56%
“…Viscosities of the lamellar mesophase formed in a ternary cationic surfactant/aromatic alcohol/water system were shown to increase with surfactant concentration, although this effect clearly vanished with increasing shear rates (Montalvo et al, 1996).…”
Section: Rheology Of Lamellar Liquid Crystals (L α α )mentioning
confidence: 96%
“…Recent studies Refs. [26,27] have reported that frequency scans for a hexagonal phase all follow the same general trend that is: G exceeds G at low frequency; at higher frequencies G and G intersect at a characteristic frequency whose reciprocal corresponds to the main relaxation time (of the order of seconds) and above this cross over frequency the phase has a predominantly elastic response. This behaviour corresponds to the transition to the flow region expected by the Maxwell model (Eq.…”
Section: Hexagonal Liquid Crystalline Phasementioning
confidence: 84%
“…Modeling of the viscoelastic properties The viscoelastic properties of the samples can be described by either using a generalized Maxwell model (Montalvo et al 1996;Steffe 1996;Subramanian and Gunasekharan 1997;Rao 1999;Ak and Gunesekharan 2001;Cuppola et al 2004) or by using power law relationship (Ortega-Ojeda et al 2004a, b, 2005Nishinari 2007). Maxwell model consists of a spring to represent the elastic and dashpot to represent the viscous nature of the viscoelastic materials connected in series.…”
Section: Dynamic Rheological Propertiesmentioning
confidence: 99%
“…Starch when heated in the presence of excess water undergoes gelatinization which involves granule swelling, amylose leaching and amylopectin fusion and upon cooling due to retrogradation, solubilized starch forms a viscous dispersion or paste or gel depending on the temperature of processing and concentration of dispersion, varieties, harvesting age and growth season Asaoka et al , 1992Defloor et al 1998;Lagarigue and Alvarez 2001;Moorthy 2001;Fourmann et al 2003). The viscoelastic behavior of starchy food systems is characterized by dynamic rheological tests and can be evaluated by Maxwell and power law models (Montalvo et al 1996;Steffe 1996;Subramanian and Gunasekharan 1997;Cortes et al 1999;Rao 1999;Ak and Gunesekharan 2001;Acharya et al 2004;Cuppola et al 2004;Ortega-Ojeda et al 2004a, b, 2005Nishinari 2007). Reports on the application of these models to quantify the viscoelastic behavior of gelated cassava starch dispersion are scanty.…”
Section: Introductionmentioning
confidence: 99%